Manual do proprietário: evolução da adequação à norma de desempenho - Brandão, Nélison Luís dos Santos; Santos, Débora de Gois; Freitas, Michelline Nei Bomfim de Santana; Mendes, Ludmilson Abritta (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The Use, Maintenance and Operation Manual is a crucial tool so that a building can keep its good performance through the years and reach its projected lifespan. The informations contained in it represent an important link between the steps of production and use of the building. However, despite its relevance, the concoction of such an important document is, many times, neglected by the builders. Therefore, with the requirements of the standard ABNT NBR 15575, it was expected a gradual improvement of the manuals – previous to the norm taking effect in July 2013 – and for them to mature in content – after mandatory normative compliance. This study aimed to assess the evolution of the level of compliance of the owner’s manuals delivered at buildings in Sergipe between 2009 and 2016 – under the requirements of NBRs 5674/12, 15575/13, and 14037/14. For that, the manuals were scored using the method proposed by Santos and Schmitt (2003); the results were statistically analyzed based on evolution and, finally, classified by levels of quality. The results show that there has been no significative evolution of the assessed manuals through the years, getting unsatisfatory grading at complying with the normative requirements.